THE UNITED STATES POLICY IN ISSUING SANCTION BILL TOWARD CHINA 2010 - Toni Rohman (2011)

(untitled)
The current issue between China and the United States over currency policy of Yuan exchange rate has given an interesting case to discus. Yuan undervalued exchange rates to the US dollar tend to increase trade protectionism by the United States. In this case the writer describes, the effect of Yuan undervalued exchange rate on trade protectionism in some points. First, the writer explain that trade protectionist movement in the United States (as measured countervailing duty and anti-dumping unde